Numerical simulation on hydrodynamic lubrication performance of bionic multi-scale composite textures inspired by surface patterns of subcrenata and clam shells. (March 2023) - Wang, Huanhuan; Lin, Naiming; Yuan, Shuo; Liu, Zhiqi; Yu, Yuan; Zeng, Qunfeng; Li, Dongyang; Fan, Jianfeng; Wu, Yucheng
Abstract: Inspired by the surface of shells in natural world, six bionic multi-scale composite surface textures were designed. Numerical simulation was carried out to investigate the mechanism for influences of the texture geometric parameters and service conditions on lubrication characteristics. The results revealed that the bionic surface enhanced the load-carrying capacity and reduced the friction coefficient. Groove combinations offered a better lubrication performance than wavy combinations. The texture geometric parameters showed significant influence on the frictional characteristics. For all texture shapes, the load-carrying capacity increased approximately linearly with the rotational speed and decreased with the water film thickness. The results would help guide effective texture design to improve the lubrication performance of axial piston pump friction pairs under marine environments. Highlights: Six bionic multiscale composite textures of different depths were designed. The effect of model parameter on the lubrication characteristics was investigated. The improvement of the lubrication performance of bionic surfaces was verified. Develop theoretical guideline for texture optimal design in marine environment.